Free to Trust? Economic Freedom and Social Capital - Niclas Berggren; Henrik Jordahl (Uppsala University, Department of Economics, 2005)
We present new evidence on how generalized trust is formed. Unlike previous studies, we look at the explanatory power of economic institutions, we use newer data, we incorporate more countries, and we use instrumental variables to handle the causality problem. A central result is that legal structure and security of property rights (area 2 of the Economic Freedom Index) increase trust. The idea is that a market economy, building on voluntary transactions and interactions with both friends and strangers within the predictability provided by the rule of law, entails both incentives and mechanisms for trust to emerge between people.
urn:nbn:se:uu:diva-79347
Keywords: K42; O40; Z13; 330; social capital; trust; economic freedom; rule of law; property rights; legal system; Social Capital; Vertrauen; Wirtschaftsliberalismus; Rechtsstaat; Eigentumsrechtstheorie